How to extract a losing intra-aortic balloon pump guide wire - Manouchehr Hekmat; Hamid Ghaderi; Seyedeh Adeleh Mirjafari; Mehran Shahzamani; Gholamreza Masoumi (International Journal of Cardiovascular Practice, 2018)
Guidewire loss is a serious complication that in case of a complete wire loss could cause death in about 20% of cases. Although it is essential to retrieve an intravenous foreign body as soon as possible, there are only a few recommendations regarding the removal of an intra-arterial foreign body. This study reports on a rare complication of guidewire loss during the insertion of an Intra-Aortic Balloon Pump (IABP), which has not yet been reported in the literature. The approach to this problem has been described, including the extraction time and the technique.